2015
DOI: 10.1111/pcmr.12410
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis of constitutive pigmentation of human epidermis reveals constant eumelanin to pheomelanin ratio

Abstract: The skin constitutive pigmentation is given by the amount of melanin pigment, its relative composition (eu/pheomelanin) and distribution within the epidermis, and is largely responsible for the sensitivity to UV exposure. Nevertheless, a precise knowledge of melanins in human skin is lacking. We characterized the melanin content of human breast skin samples with variable pigmentations rigorously classified through the Individual Typology Angle (ITA) by image analysis, spectrophotometry after solubilization wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 57 publications
8
114
0
2
Order By: Relevance
“…Mitra et al observed a high incidence of invasive melanomas independent of UV exposure in mice with a conditional, melanocyte-targeted allele of BRAF V600E and inactivating mutation in MC1R (with an analogous phenotype to red hair/fair skin in humans); however, tyrosinase deletion (with presumed loss of both eumelanin and pheomelanin production) abrogated melanoma susceptibility related to MC1R inactivation in this model. A report found the eumelanin to pheomelanin ratio in human epidermis is rather constant regardless of pigmentation, with a higher content of not only eumelanin but also pheomelanin with darker constitutive pigmentation (Del Bino et al, 2015). Yet, to our knowledge, pheomelanin levels have not been chemically measured in human epidermis and compared between the presence and absence of MC1R variants for darker and lighter phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Mitra et al observed a high incidence of invasive melanomas independent of UV exposure in mice with a conditional, melanocyte-targeted allele of BRAF V600E and inactivating mutation in MC1R (with an analogous phenotype to red hair/fair skin in humans); however, tyrosinase deletion (with presumed loss of both eumelanin and pheomelanin production) abrogated melanoma susceptibility related to MC1R inactivation in this model. A report found the eumelanin to pheomelanin ratio in human epidermis is rather constant regardless of pigmentation, with a higher content of not only eumelanin but also pheomelanin with darker constitutive pigmentation (Del Bino et al, 2015). Yet, to our knowledge, pheomelanin levels have not been chemically measured in human epidermis and compared between the presence and absence of MC1R variants for darker and lighter phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Melanin is synthesised within melanosomes in melanocytes in the basal epidermis and hair follicles, and these melanosomes mature as they are transported along melanocytic dendrites and transferred into surrounding keratinocytes . Whereas melanocyte numbers are relatively constant between individuals, the numbers and distribution of melanosomes, as well as the relative and total amounts of brown/black eumelanin and red/yellow pheomelanin, are important determinants of constitutive skin and hair colour . The benefits of pigmentation to human skin health are evident to dermatologists, but are also likely to have provided evolutionary advantages for our ancestors (reviewed in Reference).…”
mentioning
confidence: 99%
“…The ratio of eumelanin and pheomelanin can be expressed quantitatively by EPR signal through the a/b [42, 44, 45]. In this study, the ratio of pheomelanin in total melanin (~30%) measured by EPR is similar with that in mammal skin and hair, which have a constant level of about 26% [23, 39, 44, 46]. EPR spectrum of the melanin extract from the Red scallops indicates that they contain a mixed type of pheomelanin and eumelanin in their pigmented shells.…”
Section: Discussionmentioning
confidence: 60%
“…In land animals, the colors in feathers, fur and skin are largely determined by melanocytes, which are responsible for melanin production, and melanin is the main contributor to their pigmentation [22]. The quantity, quality, and distribution of melanin contents in animal tissues are usually correlated with the visual phenotypes of their pigmentation [7, 11, 23]. In contrast, the nature of melanin is far from being well understood in molluscs, such as bivalves, although melanin is almost certainly common in their shells [15].…”
Section: Introductionmentioning
confidence: 99%